An Overview of COVID-19 Impacts on Commercial E-Commerce Platforms in Southeast Asia Region - Zailani Abdullah; Noorshella Che Nawi (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus in Wuhan, China. Due to this pandemic, almost all countries in Southeast Asia had executed either lockdown or state of emergency action. However, an online marketplace via an E-Commerce platform is still needed to operate and also directly affected by this pandemic. Therefore, this overview reveals the impacts of the top 3 E-commerce platforms during pandemic COVID-19 with regard to the consumers in the Southeast Asia region (specifically in Malaysia, Indonesia & Thailand). Design/methodology/approach: Due to the COVID-19 pandemic, the revenue of E-commerce platforms companies might be slightly a bit dropped due to uncertainty factors in the countries that have been affected by this virus. Indeed many countries around the globe already implemented and still progressing either lockdown or state of emergency protocol. In this study, we selected the top three E-commerce platforms in Southeast Asia namely Lazada, Shopee, and Tokopedia. Findings: The results found that there were several initiations by them to battle against COVID-19. In addition, there are still a lot of improvements that can be effectively played by them. Research limitations/implications: This research is a literature review research. Practical implications: The result of this research can be used as references to run a digital business. Originality/value: This paper is original. Paper type: Research paper